SimpleHRTF-3D: From Head Mesh to Immersive Spatial Audio - Mendonça, Augusto M. P. de; Santana, Abraão de; Teixeira, Jan M.; Silva, Kedson A.; Ferro, Mariza; Coelho, Igor M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16045, 2025)
Head-Related Transfer Functions (HRTFs) are essential for immersive spatial audio in multimedia applications like virtual reality and gaming, yet personalization remains challenging due to precise anthropometric measurement requirements. This paper introduces an open source pipeline for HRTF customization through three objectives. First, we validate a published Random Forest model on HUTUBS, achieving similar R2=89.8% and SD=4.45 dB with manual measures. Second, SimpleHRTF-3D automates extraction from 3D head meshes using two-step PSO, achieving 10.96% mean extraction error (a 2.31 percentage point absolute reduction from 13.27% single-step error), yielding R2=89.3% and SD=5.04 dB. As proof of concept, we extended the method to use photogrammetry, enabling photo-to-HRTF personalization. Validated on 58 HUTUBS subjects, our pipeline integrates manual, mesh, and image methods, providing reproducible tools for multimedia HRTF adaptation. The results demonstrate high-fidelity spatial audio capabilities for diverse immersive applications.